posted by Jeana on .
*I think that the first two use F.O.I.L but i still cant get it
I'm afraid I do not catch your question.
Are you supposed to find f(4b) when f(x)=4x^2+5x-5? Or are you supposed to find f(x) when f(4b)=4x^2+5x-5. The second option does not make sense because the expression f(4b) should not leave any trace of "x" when x=4b.
Would the question then be:
If f(x)=4x^2+5x-5, find f(4b).
In this case,
f(4b)= 4(4b)² + 5(4b) -5
= 4(16b²) + 20b -5
= 64b² + 20b -5
Okay thank you that really makes more since your a lifesaver! Do you know how to do number 2 and 3 that you could walk me through too? I have literally tried them 11 times and it still says they are wrong
First step: write down the function in terms of x:
Then substitute x by what is in the parentheses (x+1) in this case. Don't forget the parentheses everywhere you make a substitution:
f(x+1)=8(x+1)² + (x+1) - 3
Expand and collect terms as required:
=8(x+1)² + (x+1) - 3
=8(x²+2x+1) + x+1 -3
=8x² + 16x + 8 +x+1 -3
=8x² + 17x + 6
Proceed the same way for number 3. Post for checking if necessary. The answer is 8x²-x-3.